2021
DOI: 10.3390/ma14185310
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Geocomposite Properties on the Crack Propagation and Interlayer Bonding of Asphalt Pavements

Abstract: The application of geocomposites as reinforcement in asphalt pavements is a promising solution for the maintenance/rehabilitation of existing pavements and for the construction of new pavements, whose effectiveness strongly depends on the physical and mechanical properties of the geocomposite. This study aims at assessing the influence of four different geocomposites, obtained by combining a reinforcing geosynthetic with a bituminous membrane, on the crack propagation and interlayer bonding of asphalt pavement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Many scientific proofs encourage using geosynthetic materials as an interlayer between bituminous layers to restrict fatigue cracking and rutting and to delay the appearance of reflective cracking ( 10 ). This rehabilitation solution not only acts as a stress relief and reinforcement layer in the system ( 11 ) but, also compared to a thick overlay, it is much more cost-effective ( 12 ) and sustainable since it allows lower hot mix materials as an overlay, thus decreasing the level of emissions and dissipation of natural sources of materials ( 7 ). However, the degree of effectiveness of the reinforced system depends mostly on the bounding condition provided at the interface ( 13 ).…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scientific proofs encourage using geosynthetic materials as an interlayer between bituminous layers to restrict fatigue cracking and rutting and to delay the appearance of reflective cracking ( 10 ). This rehabilitation solution not only acts as a stress relief and reinforcement layer in the system ( 11 ) but, also compared to a thick overlay, it is much more cost-effective ( 12 ) and sustainable since it allows lower hot mix materials as an overlay, thus decreasing the level of emissions and dissipation of natural sources of materials ( 7 ). However, the degree of effectiveness of the reinforced system depends mostly on the bounding condition provided at the interface ( 13 ).…”
Section: Research Backgroundmentioning
confidence: 99%
“…When the interlayer has higher stiffness than its surrounding asphaltic material, the crack path diverts horizontally along the interlayer plane until the whole energy of the crack dissipates by stretching the interlayer under the movement. Current laboratory test devices that permit measuring the crack resistance of asphalt overlays are able to apply concurrently shear, tensile, and flexural stresses in the proximity of the crack and provide a stable state of crack propagation: the four-point bending test (1)(2)(3), wheel reflective cracking (WRC) test (4,5), wedge splitting test method (5), direct tensile strength test (6), modified wheel tracker (7), Texas overlay tester (8), and UGR-FACT (9) are just a few. However, because of demanding large-size specimens, manipulation, and preparation of specimens, the complexity of the analysis of the results and less suitability in incorporating the reinforced structures with geosynthetics, the universal acceptability of these tests methods is limited in practice.…”
mentioning
confidence: 99%
“…Hwang (2018) noted that applying an asphalt overlay to the existing concrete pavement can increase shear adhesion strength due to the interlocking effect between the concrete floor plate and the asphalt layer and the increased surface area coated with the tack coat [23]. In the case of the simultaneous laying method, adhesion performance may be affected by the use of different materials and the condition of the aged concrete pavement [48]. Therefore, in this study, the tack coat adhesion performance was evaluated by simulating the maintenance process of old concrete pavement.…”
Section: Shear Adhesion Strength Testmentioning
confidence: 99%
“…Ragni et al [10] assessed the effectiveness of asphalt pavement rehabilitation with geocomposites to limit fatigue cracking, reflective cracking, and rutting. Kumar et al [11] evaluated the cracking resistance potential of geosynthetic-reinforced asphalt overlays by using a direct tensile strength test at 20, 30, and 40 • C. He pointed out that the performance of specimens conditioned at temperatures of 20 • C is superior to those at 30 and 40 • C. Spadoni et al [12] assessed the influence of four different geocomposites, obtained by combining a reinforcing geosynthetic with a bituminous membrane, regarding the crack propagation and interlayer bonding of asphalt pavements. The threepoint bending test was carried out on double-layered asphalt specimens at temperatures of 20 • C. Results showed that the main contribution of the geocomposites consisted in increasing the crack propagation energy in the layer above the reinforcement (from five to ten times with respect to the unreinforced system).…”
Section: Introductionmentioning
confidence: 99%